Protective Effects of Dexazoxane on Rat Ferroptosis in Doxorubicin-Induced Cardiomyopathy Through Regulating HMGB1 - Zhang, Haiyan; Wang, Zheng; Liu, Zhengxia; Du, Kang; Lu, Xiang (Frontiers in Cardiovascular Medicine, 2021)
Dexrazoxane (DXZ) reduces cytotoxicity caused by Doxorubicin (DOX). However, the mechanism of DXZ in ferroptosis and cardiomyopathy remains unclear. This research, therefore, explores the role and mechanism of DXZ in DOX-induced ferroptosis and cardiomyopathy in rats. Kaplan–Meier survival analysis was performed in rats treated by DOX in combination with ferroptosis inhibitor (FER-1) or other cell death–associated inhibitors. The ferroptosis, cardiotoxicity, and expression of high mobility group box 1 (HMGB1) in rats treated by DOX in combination with FER-1 or with DXZ were determined by hematoxylin and eosin staining, echocardiographic analysis, and quantitative real-time PCR. The ferroptosis in DOX-treated rats that received HMGB1 knockdown or overexpression was further detected using molecular experiments. Finally, the viability, level of malondialdehyde (MDA), and expressions of ferroptosis-related markers (PTGS2, GPX4, and FTH1) of rat cardiomyocyte H9c2 exposed to DOX combined with FER-1, zVAD (an apoptosis inhibitor), DXZ, or not were detected by performing molecular experiments. FER-1 increased the survival of the rats induced by DOX. The DOX-induced ferroptosis and cardiotoxicity could be reversed by FER-1 or DXZ. HMGB1 was induced by DOX but was inhibited by DXZ or FER-1. Overexpression of HMGB1 promoted the ferroptosis and cardiotoxicity induced by DOX in the rats although silencing of HMGB1 showed opposite effects. The data indicate that DOX suppressed the viability and increased the MDA level in H9c2 cells in a dose-dependent manner. Moreover, DOX-induced increase of PTGS2 and decrease of GPX4 and FTH1 in H9c2 cells was reversed by DXZ or FER-1. Therefore, DXZ has protective effects on ferroptosis and cardiomyopathy in rats through regulating HMGB1.